2014
DOI: 10.1074/jbc.c114.571026
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Histidyl-tRNA Synthetase Splice Variants Elaborate Major Epitopes for Autoantibodies in Inflammatory Myositis

Abstract: Background: Autoantibodies (anti-Jo-1) to cytoplasmic histidyl-tRNA synthetase (HisRS) are associated with inflammatory myositis. Results: HisRS and two splice variants (SVs) cross-react with anti-Jo-1 antibodies and are secreted; at least one SV transcript is up-regulated in dermatomyositis. Conclusion: Secreted HisRS SVs contain major epitopes of anti-Jo-1 autoantibodies. Significance: Secreted HisRS and its SVs share epitopes for potential extracellular anti-Jo-1 antibody binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 48 publications
1
41
0
1
Order By: Relevance
“…Because other tRNA synthetases not linked to the anti-synthetase syndrome do not manifest similar chemokine profiles [23], these studies also suggest that the capacity to activate innate immune signaling pathways is a key factor contributing to antigenicity and disease pathogenesis. More recent studies demonstrating upregulated mRNA expression of secretable splice variants of HRS (recognized by autoantibodies) in muscle tissue of dermatomyositis patients [24] support this hypothesis and suggest a mechanism by which altered forms of this protein elaborated in a tissue-specific Table 1 Role of Jo-1/HRS in adaptive vs. innate immunity Adaptive immunity Jo-1-specific T cells detected in peripheral blood of myositis patients Anti-Jo-1 antibodies undergo affinity maturation Anti-Jo-1 antibodies correlate with disease activity Jo-1/CFA immunization of mice generates species-specific immune responses, myositis, and ILD Innate immunity…”
Section: Jo-1-mediated Activation Of Innate Immune Signaling Pathwaysmentioning
confidence: 98%
“…Because other tRNA synthetases not linked to the anti-synthetase syndrome do not manifest similar chemokine profiles [23], these studies also suggest that the capacity to activate innate immune signaling pathways is a key factor contributing to antigenicity and disease pathogenesis. More recent studies demonstrating upregulated mRNA expression of secretable splice variants of HRS (recognized by autoantibodies) in muscle tissue of dermatomyositis patients [24] support this hypothesis and suggest a mechanism by which altered forms of this protein elaborated in a tissue-specific Table 1 Role of Jo-1/HRS in adaptive vs. innate immunity Adaptive immunity Jo-1-specific T cells detected in peripheral blood of myositis patients Anti-Jo-1 antibodies undergo affinity maturation Anti-Jo-1 antibodies correlate with disease activity Jo-1/CFA immunization of mice generates species-specific immune responses, myositis, and ILD Innate immunity…”
Section: Jo-1-mediated Activation Of Innate Immune Signaling Pathwaysmentioning
confidence: 98%
“…This study showed that a bacteria-derived virulence factor could use KRS as a cytokine to synergistically exacerbate inflammatory responses in the host. HRS secreted in its full-length form [97] induced lymphocyte migration and activated monocytes and immature dendritic cells through CCR5 binding [98].…”
Section: Secreted Arss Acting As Cytokines and Chemokinesmentioning
confidence: 99%
“…Resolaris (histidyl-tRNA synthetase, aTyr Pharma, Inc., San Diego, CA, USA) has been shown to reverse immune cell invasion of muscle tissue in an animal model of myopathy [30]. Furthermore, autoantibodies to cytoplasmic histidyl-tRNA synthetase have been associated with inflammatory myositis [31]. A multinational Phase Ib/II clinical trial of this agent in adult patients with FSHD is under way in Europe.…”
Section: Investigational Agents For Fshdmentioning
confidence: 98%